The Role of Government in Overcoming Industrial Development Impact towards Environmental Sustainability - Bayu Mitra Adhyatma Kusuma (Graduate Program, 2014)
Indonesia is actively implementing of national development. In order to realize the national development, the government has tried to do various efforts. One of them is pushing the pace of the national economy. The industrial sector is the mainstay of the government to boost the economy in Indonesia. Developments in the industry cannot be separated from the utilization of natural resources; both renewable resources and non-renewable resources. But on the other hand, the industrial development has a negative impact on the creatures and the environment. Development in the industrial sector has led to a variety of effects such as increased pollution resulting from industrial production processes to ecological disaster. The facts of environmental damage that occurred in Indonesia today should be seen as a whole and comprehensive for immediate rescue efforts. As we know, in Indonesia has implemented Government Regulation No. 27 Year 1999 on Environmental Impact Assessment (EIA). However, the environmental pollution caused by the industrial sector development is still happening today. The results of research show that there are three basic principles that made by the government to control the environmental damage caused by the industrial development, namely administratively, technologically, and instructively. Industrial development is a process that moves in a straight line, from the backward communities to advance society. But promoting the advancement of society should not be paid for environmental damage. It should be the role of government and public awareness to run environmentally sound technology and environmentally sound development to solve these issues. In this research the author used qualitative research type, descriptive approach and emphasis in literature study. Keywords: Role of Government, Industrial Development, Environmental Sustainability